Serum zinc concentrations and indices of inflammatory response and serum IgA in children with infectious diarrhea - Pechuhina, V. V.; Usachova, O. V. (Pathologia, 2024)
Аim. The objective of this study was to give a comparative characteristic of laboratory manifestations for the inflammatory process and the level of serum IgA in infectious diarrhea in young children, depending on serum zinc concentrations. Materials and methods. The study included 99 children aged 1 to 36 months with the clinical picture of infectious diarrhea. The main group was divided into the first subgroup comprising 77 children with normal blood zinc level during hospitalization; the second contained 22 children with reduced blood zinc level. On the day of hospitalization, the level of C-reactive protein (CRP), zinc (Zn) and the presence of fecal calprotectin (FC) and lactoferrin (LF) were determined. The level of interleukins and serum IgA was determined in 34 children of the main group (16 for the first subgroup, and 18 for the second one) on the 1st, 3rd and 5th days. The comparison group consisted of 10 children without signs of infectious pathology. Results. There were no significant differences between the subgroups in terms of the frequency of registering an increase in blood CRP level (in 21 children (27.27 %) of the first subgroup, and 7 children (31.81 %) of the second one) and its level. Qualitatively determined FC and LF did not demonstrate any significant difference between the comparison subgroups. The level of IL-10 in the blood serum of children of both subgroups was higher than that of the comparison group (p = 0.001 for the first subgroup and p = 0.04 for the second). In the dynamics, the concentration of IL-10 tended to decrease in patients with a reduced blood Zn level. The level of IL-1β in the first subgroup (0.28 (0.12; 0.68) pg/ml) corresponded to the indicators of healthy children (0.32 (0.12; 0.78) pg/ml). Patients of the second subgroup had lower concentrations of IL-1β (p = 0.05). In the dynamics, a significant increase in the concentration of this cytokine was noted in patients of the second subgroup, but it remained significantly lower than in healthy subjects (p = 0.01). The concentration of IL-6 in the serum of children in the comparison subgroups did not differ statistically both at the onset of the disease and in the dynamics. The level of serum IgA on the fifth day of treatment was significantly reduced in children with a reduced blood Zn level (p = 0.03). Conclusions. Blood CRP, PC, and GFR did not show dependence on serum Zn concentration in children with infectious diarrhea. Children with low Zn levels at the onset of the disease have an imbalance in the inflammatory response system. In children with low blood Zn concentration, a decrease in the concentration of serum IgA on the fifth day of treatment was determined.